Positive pole piece and battery

By setting a positive electrode active material coating in the positive electrode sheet of the lithium manganese iron phosphate thick electrode battery and adjusting the material content relationship, the problems of poor conductivity and serious cyclic attenuation are solved, and a higher battery capacity retention rate and lower DC internal resistance are achieved.

CN119695058AActive Publication Date: 2025-03-25EVE POWER CO LTD
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411657861.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-25
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

Existing lithium manganese iron phosphate thick electrode batteries have poor conductivity and serious attenuation in the later cycle, which is difficult to meet the demand for battery energy density of high-end new energy vehicles.

Method used

By providing a positive electrode active material coating in the positive electrode sheet, the coating includes the positive electrode active material, the conductive material and the binder, and adjusting the compaction density, the content relationship between the conductive material and the binder to satisfy the range of 0.27≤Wn/(PD*Wd)≤1.12.

Benefits of technology

The appropriate compaction density, conductivity and circulation capability of the positive electrode sheet are achieved, and the overall performance of the battery is improved, including higher capacity retention and lower DC internal resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119695058A_ABST
    Figure CN119695058A_ABST
Patent Text Reader

Abstract

The invention provides a positive pole piece and a battery. The positive pole piece comprises a positive current collector and a positive active material coating arranged on at least one surface of the positive current collector, the positive active material coating comprises a positive active material, a conductive material and a binder; wherein the relationship among the compaction density PD of the positive pole piece, the content Wd of the conductive material and the content Wn of the binder meets the condition that Wn / (PD * Wd) is greater than or equal to 0.27 and less than or equal to 1.12. When the content and the compaction density of the conductive material and the binder of the positive pole piece provided by the invention meet the relation and the range, the battery applying the positive pole piece has relatively excellent conductivity and cycle capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode sheet and a battery. Background Art

[0002] At present, the demand for new energy vehicles with long driving range forces the requirements for battery energy density to become higher and higher. The use of thick electrodes with high load density active materials is one of the most practical strategies. However, during the long cycle use, the thick electrodes are accompanied by severe attenuation of electrochemical performance, power performance cannot be met, and capacity retention rate is getting worse and worse. Due to the differences in basic properties such as conductivity and particle size of thick electrode materials themselves, this phenomenon of thick electrode cycle attenuation is particularly prominent in lithium manganese iron phosphate (compared with ternary and iron lithium materials). Therefore, the current lithium manganese iron phosphate thick electrode battery has poor conductivity and severe attenuation in the late cycle. Summary of the invention

[0003] The embodiments of the present invention provide a positive electrode plate and a battery, which have both good conductivity and high cycle capacity.

[0004] In order to achieve the above-mentioned object, according to a first aspect of the present application, there is provided a positive electrode sheet, comprising a positive electrode current collector and a positive electrode active material coating disposed on at least one surface of the positive electrode current collector;

[0005] The positive electrode active material coating comprises a positive electrode active material, a conductive material and a binder;

[0006] The compaction density PD of the positive electrode sheet and the content W of the conductive material d And the content of the binder W n The relationship satisfies: 0.27≤W n / (PD*Wd)≤1.12.

[0007] In some embodiments, the conductive material includes a main conductive agent and an auxiliary conductive agent, the main conductive agent is in a granular form, and the auxiliary conductive agent is in a linear structure.

[0008] In some embodiments, the primary conductive agent includes carbon black, and the auxiliary conductive agent includes at least one of carbon nanotubes and carbon nanofibers.

[0009] In some embodiments, the conductive material includes carbon black and carbon nanotubes, wherein the mass percentage a of the carbon black ranges from 0.3% to 1.8%, the mass percentage b of the carbon nanotubes ranges from 0.2% to 0.8%, and a>b.

[0010] In some embodiments, the conductive material includes carbon black and carbon nanofibers, wherein the mass percentage a of the carbon black ranges from 0.3% to 1.8%, the mass percentage c of the carbon nanofibers ranges from 0.2% to 0.8%, and a>c.

[0011] In some embodiments, the conductive material includes carbon black, carbon nanotubes and carbon nanofibers, wherein the mass percentage a of the carbon black ranges from 0.3% to 1.8%, the mass percentage b of the carbon nanotubes ranges from 0.2% to 0.8%, the mass percentage c of the carbon nanofibers ranges from 0.2% to 0.8%, and a≥b≥c.

[0012] In some embodiments, the thickness of the positive electrode sheet is d, 200 μm ≤ d ≤ 250 μm; the surface density of the positive electrode sheet is SD, 480 g / m 2 ≤SD≤560g / m 2 The compaction density of the positive electrode is PD, 2.3g / cm 3 ≤PD≤2.5g / cm 3 .

[0013] In some embodiments, the positive electrode active material includes lithium manganese iron phosphate.

[0014] In some embodiments, in the positive electrode active material coating, the mass percentage of the positive electrode active material ranges from 96% to 98%, the mass percentage of the conductive material ranges from 0.8% to 1.8%, and the mass percentage of the binder ranges from 1.2% to 2.2%.

[0015] According to a second aspect of the present application, a battery is provided, comprising the positive electrode plate as described in the first aspect.

[0016] The present application provides a positive electrode sheet and a battery. The positive electrode sheet of the present application includes a positive electrode active material coating, and the positive electrode active material coating includes a positive electrode active material, a conductive material, and a binder; wherein the compaction density PD of the positive electrode sheet and the content W of the conductive material d And the binder content W n The relationship satisfies: 0.27≤W n / (PD*Wd)≤1.12. This application comprehensively considers the compaction density PD of the positive electrode sheet and the content W of the conductive material. d , binder content W n The coordination relationship between them is n / (PD*W d) is in the range of 0.27 to 1.12, the positive electrode active material coating has a suitable compaction density, a suitable conductive material content and a binder content, so that the battery using the positive electrode sheet has both good conductivity and high cycle capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application, and those skilled in the art can obtain other drawings based on these drawings without creative work.

[0018] Figure 1 It is a schematic diagram of the structure of a positive electrode plate provided in an embodiment of the present application. DETAILED DESCRIPTION

[0019] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0020] The present application provides a positive electrode sheet, which includes a positive electrode current collector and a positive electrode active material coating disposed on at least one surface of the positive electrode current collector; the positive electrode active material coating includes a positive electrode active material, a conductive material, and a binder; wherein the compaction density PD of the positive electrode sheet and the content W of the conductive material d And the binder content W n The relationship satisfies: 0.27≤W n / (PD*Wd)≤1.12.

[0021] See also Figure 1 , is a schematic diagram of the structure of a positive electrode plate provided in an embodiment of the present application, the positive electrode plate 10 includes a positive electrode collector 1, the positive electrode collector 1 has a first surface 11 and a second surface 12 opposite to each other, and the positive electrode active material coating 2 is located on the first surface 11 and / or the second surface 12. In the present application, the material of the positive electrode collector 1 can be a metal, such as aluminum or copper, but is not limited thereto. The positive electrode active material coating 2 is formed on the first surface 11 and / or the second surface 12 of the positive electrode collector 1 through coating, drying, rolling and other processes. Specifically, as Figure 1 As shown, the positive electrode plate 10 can be coated on both sides of the positive electrode collector 1 by a single-layer coating process, that is, the positive electrode active material coating 2 on the first surface 11 and the second surface 12 of the positive electrode collector 1 are both single-layer film layers.

[0022] The compaction density PD of the positive electrode plate refers to the ratio of the surface density SD of the positive electrode plate after rolling to the thickness d of the positive electrode plate, PD = SD / d, where d does not include the thickness of the positive current collector. The compaction density PD has a great influence on the battery performance. It is closely related to the specific capacity, efficiency, internal resistance of the plate and the cycle performance of the battery. Generally speaking, the greater the compaction density, the higher the capacity of the battery, so the compaction density is regarded as an important reference indicator for the energy density of the electrode material. However, too large or too small a compaction density is not conducive to the embedding and extraction of lithium ions. When the compaction density is too large, the degree of extrusion between the electrode material particles will be greater, the porosity of the plate will be smaller, the channels available for ion transmission will be reduced, the performance of the plate in absorbing the electrolyte will be worse, and the electrolyte will be difficult to infiltrate, resulting in large polarization losses and greater attenuation during the battery cycle, and a significant increase in internal resistance. When the compaction density is too small, it not only increases the ion transmission distance, but also is not conducive to the capacity improvement of the battery. Therefore, a suitable compaction density can increase the capacity of the battery, reduce the internal resistance, reduce the polarization loss, and extend the cycle life of the battery. In this application, the compaction density PD of the positive electrode sheet is in the range of 2.3 g / cm 3 ≤PD≤2.5g / cm 3 When the compaction density PD of the positive electrode sheet is within the above range, the battery has a higher capacity without affecting the kinetic performance.

[0023] The surface density SD of the positive electrode sheet refers to the density of the positive electrode active material coating on the positive electrode current collector per unit area. In this application, the surface density SD of the positive electrode sheet refers to the double-sided surface density. The surface density SD of the positive electrode sheet is in the range of 480g / m 2 ≤SD≤560g / m 2 When the surface density SD of the positive electrode is within the above range, the battery has a better endurance. When the surface density SD is too low, the battery capacity is too small, resulting in insufficient endurance; when the surface density SD is too high, there is a problem of insufficient dynamics on the one hand, and on the other hand, it will lead to an increase in manufacturing costs.

[0024] In the present application, the thickness d of the positive electrode plate is in the range of 200 μm≤d≤250 μm. The positive electrode plate of the present application is a thick electrode. The use of a thick electrode can increase the energy density of the battery and improve the battery life.

[0025] In the prior art, thick electrodes have poor conductivity and serious decay in the later stages of cycles. d , binder content W n The coordination relationship between them makes the three satisfy 0.27≤W n / (PD*Wd)≤1.12, when W n / (PD*W d) is in the range of 0.27 to 1.12, so that the positive electrode sheet has a suitable compaction density, a suitable conductive material content and a binder content, which can improve the capacity and conductivity of the positive electrode sheet while taking into account the bonding force between the positive electrode sheet and the positive current collector, thereby improving the cycle capacity of the battery under thick electrodes and improving the overall performance of the battery.

[0026] In the present application, the positive electrode active material coating includes a positive electrode active material, a conductive material and a binder, wherein the mass percentage of the positive electrode active material is W h The range is 96% to 98%, and the mass percentage of the conductive material W d The range is 0.8% to 1.8%, and the mass percentage of the binder W n The range of is 1.2% to 2.2%. In the positive electrode active material coating, the sum of the mass percentage of the positive electrode active material, the mass percentage of the conductive material and the mass percentage of the binder is W h +W d +W n =100%. When the contents of the positive electrode active material, the conductive material and the binder are within the above ranges, the positive electrode sheet has better conductivity and the battery has better cycle capacity.

[0027] In the present application, the positive electrode active material may be lithium manganese iron phosphate (LMFP). In the prior art, thick lithium manganese iron phosphate electrodes have the problems of poor conductivity and severe decay in the late cycle. In the present application, the compaction density PD of the positive electrode sheet and the content W of the conductive material are increased. d , binder content W n Satisfy 0.27≤W n / (PD*Wd)≤1.12, which makes the thick electrode lithium manganese iron phosphate battery have better conductivity and cycle capacity.

[0028] In the present application, the conductive material includes a main conductive agent and an auxiliary conductive agent. The main conductive agent is granular, such as carbon black, acetylene black, Ketjen black, etc. The auxiliary conductive agent is a linear structure, which can be a long chain structure or a tubular structure. These linear conductive agents have a large aspect ratio, among which long chain structure conductive agents such as carbon nanofibers, tubular structure conductive agents such as carbon nanotubes, etc. The main conductive agent is granular, has strong conductivity and good dispersibility, and the auxiliary conductive agent is a linear structure that can form a network structure and construct a conductive path. By adding an auxiliary conductive agent with a linear structure to the main conductive agent, the main conductive agent and the auxiliary conductive agent form a conductive network together, which is beneficial to improving the overall conductivity of the conductive material, and then improving the conductive performance of the positive electrode sheet.

[0029] In some embodiments, the main conductive agent includes carbon black, and the auxiliary conductive agent includes at least one of carbon nanotubes and carbon nanofibers. Among them, the particle size range of carbon black is 10nm-50nm. Carbon black has high conductivity, small particle size, large specific surface area, and easy dispersion, which is conducive to improving conductivity and electrochemical performance. Carbon nanotubes have a hollow structure, with a diameter range of 1nm-20nm and a length range of 0.5um-15um. Carbon nanotubes can withstand the volume change of positive electrode active materials during battery expansion, reducing particle breakage and structural damage. Carbon nanofibers are linear non-hollow structures with a diameter range of 60nm-200nm and a length range of 30um-100um. They can bridge the gaps between positive electrode active material particles to ensure electron and ion transmission. Both carbon nanotubes and carbon nanofibers are linear structures that can form a mesh structure and form a conductive network together with the main conductive agent, which is conducive to improving the overall conductivity of the conductive material, thereby improving the conductive performance of the positive electrode sheet.

[0030] In one embodiment, the conductive material includes carbon black and carbon nanotubes, wherein the mass percentage a of the carbon black ranges from 0.3% to 1.8%, the mass percentage b of the carbon nanotubes ranges from 0.2% to 0.8%, and a>b.

[0031] In this embodiment, carbon nanotubes can form a conductive network with carbon black, and the carbon nanotubes have a hollow structure and can be used as a particle transmission channel, which can effectively improve the conductivity of the conductive material. The content of carbon nanotubes must be less than that of carbon black, and the content of carbon nanotubes should not be too much. Too much carbon nanotube content will lead to a decrease in the porosity of the conductive material, poor electrolyte infiltration, and poor dispersion of the conductive material, which is prone to agglomeration, resulting in an increase in local charge and an increase in side reactions, which in turn affects the conductive performance.

[0032] In one embodiment, the conductive material includes carbon black and carbon nanofibers, wherein the mass percentage a of the carbon black ranges from 0.3% to 1.8%, the mass percentage c of the carbon nanofibers ranges from 0.2% to 0.8%, and a>c.

[0033] In this embodiment, carbon nanofibers can form a conductive network with carbon black. Carbon nanofibers have a long chain structure and are more likely to form a mesh structure, construct a conductive path between carbon black particles, and effectively improve the conductive properties of the conductive material. The content of carbon nanofibers must be less than that of carbon black, and the content of carbon nanofibers should not be too much. Too much carbon nanofiber content will lead to a decrease in the porosity of the conductive material, poor electrolyte infiltration, and difficulty in dispersing active materials and carbon black, resulting in agglomeration, which in turn affects the conductive properties.

[0034] In one embodiment, the conductive material includes carbon black, carbon nanotubes and carbon nanofibers, wherein the mass percentage a of the carbon black ranges from 0.3% to 1.8%, the mass percentage b of the carbon nanotubes ranges from 0.2% to 0.8%, the mass percentage c of the carbon nanofibers ranges from 0.2% to 0.8%, and a≥b≥c.

[0035] In this embodiment, carbon nanotubes, carbon nanofibers and carbon black together form a conductive network, among which the carbon nanotubes have better conductivity than carbon nanofibers, and have higher strength and flexibility, which can avoid the failure of the positive electrode material caused by volume expansion and contraction during charging and discharging. The conductivity and stability of carbon nanofibers are slightly lower than those of carbon nanotubes, but structurally they have a larger diameter and longer length than carbon nanotubes, and can be composited with carbon nanotubes to further enhance the conductive properties of the conductive material and enhance the comprehensive performance of the conductive material.

[0036] In the present application, the binder is used to increase the adhesion between the materials of the positive electrode active material coating and the adhesion between the positive electrode active material coating and the positive electrode current collector to improve the stability and life of the battery. The binder can be, but is not limited to, one or more of polyvinylidene fluoride (PVDF), styrene butadiene rubber (SBR), polyacrylic acid (PAA), etc.

[0037] The present application also provides a method for preparing a positive electrode sheet, comprising:

[0038] Adding positive electrode active material, conductive material and binder into solvent and mixing to form positive electrode slurry;

[0039] Applying the positive electrode slurry to at least one surface of the positive electrode current collector, and forming a positive electrode sheet after drying and rolling;

[0040] Among them, the compaction density PD of the positive electrode sheet and the content of the conductive material W d And the binder content W n The relationship satisfies: 0.27≤W n / (PD*Wd)≤1.12.

[0041] The present application also provides a battery, which includes a battery casing, an electrolyte, a negative electrode plate, a separator and the positive electrode plate as above, which are located in the battery casing.

[0042] The battery shell has a receiving cavity, in which the negative electrode sheet, the separator, and the positive electrode sheet are stacked in sequence, and the electrolyte is contained in the receiving cavity. The material of the battery shell can be metal, such as aluminum, steel, etc.

[0043] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material coating disposed on at least one surface of the negative electrode current collector, and the negative electrode active material coating may include graphite, a conductive agent, a binder, etc. The conductive agent may be carbon black, acetylene black, Ketjen black, etc., and the binder may be a styrene-butadiene rubber (SBR) solution, a polyacrylate solution, etc.

[0044] The positive electrode sheet and the battery of the present application are further described below through specific embodiments.

[0045] 1. Battery preparation method

[0046] (1) Preparation of positive electrode sheet

[0047] S11, the positive electrode active material, the conductive material and the binder are mixed with W h :W d :W n The mass ratio of is added into N-methylpyrrolidone (NMP), mixed, and stirred evenly to obtain a positive electrode slurry; and

[0048] S12, coating a single layer of the positive electrode slurry on the two surfaces of the positive electrode collector, drying, and rolling to obtain a positive electrode sheet, wherein the surface density of the positive electrode sheet is SD, and the compaction density of the positive electrode sheet is PD.

[0049] (2) Preparation of negative electrode sheet

[0050] S21, mixing graphite, carbon black and styrene-butadiene rubber (SBR) in a mass ratio of 97.3:1.5:1.2, adding the mixture to a solvent, and stirring the mixture to obtain a negative electrode slurry; and

[0051] S22, applying a single layer of the negative electrode slurry onto the two surfaces of the negative electrode current collector, drying, and rolling to obtain a negative electrode sheet.

[0052] S3. Preparation of batteries

[0053] The vacuum-dried positive electrode sheets, separators and negative electrode sheets are assembled and then cut, die-cut, striped and placed in the battery casing. The electrolyte is then injected under high temperature and negative pressure to assemble into a square aluminum shell battery.

[0054] The batteries corresponding to Examples 1 to 8 were prepared by the above-mentioned battery preparation method. Among them, the positive electrode sheets, negative electrode sheets and battery preparation methods of Examples 1 to 8 are the same and will not be described in detail. The only difference between Examples 1 to 8 is the ratio of the positive electrode active material, conductive material and binder of the positive electrode sheet, the composition and ratio of the conductive agent or the compaction density. For details, please refer to the following examples and Table 1.

[0055] Embodiment 1:

[0056] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black, carbon nanotubes and carbon nanofibers, and the binder is polyvinylidene fluoride (PVDF);

[0057] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =97:1.3:1.7; the mass ratio of carbon black, carbon nanotubes and carbon nanofibers in the conductive material is a:b:c=0.6:0.4:0.3;

[0058] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.3g / cm 3 .

[0059] Embodiment 2:

[0060] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black, carbon nanotubes and carbon nanofibers, and the binder is polyvinylidene fluoride (PVDF);

[0061] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =96.2:1.8:2; the mass ratio of carbon black, carbon nanotubes and carbon nanofibers in the conductive material is a:b:c=0.8:0.6:0.4;

[0062] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.45g / cm 3 .

[0063] Embodiment 3:

[0064] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black, and the binder is polyvinylidene fluoride (PVDF);

[0065] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =97:1.3:1.7;

[0066] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.3g / cm 3 .

[0067] Embodiment 4:

[0068] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black and carbon nanotubes, and the binder is polyvinylidene fluoride (PVDF);

[0069] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =97:1.3:1.7; the mass ratio of carbon black and carbon nanotubes in the conductive material is a:b=0.7:0.6;

[0070] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.3g / cm 3 .

[0071] Embodiment 5:

[0072] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black and carbon nanotubes, and the binder is polyvinylidene fluoride (PVDF);

[0073] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =97:1.3:1.7; the mass ratio of carbon black and carbon nanotubes in the conductive material is a:b=0.5:0.8;

[0074] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.3g / cm 3 .

[0075] Embodiment 6:

[0076] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black, carbon nanotubes and carbon nanofibers, and the binder is polyvinylidene fluoride (PVDF);

[0077] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =97:1.3:1.7; the mass ratio of carbon black, carbon nanotubes and carbon nanofibers in the conductive material is a:b:c=0.3:0.4:0.6;

[0078] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.3g / cm 3 .

[0079] Embodiment 7:

[0080] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black, carbon nanotubes and carbon nanofibers, and the binder is polyvinylidene fluoride (PVDF);

[0081] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =97:1.8:1.2; the mass ratio of carbon black, carbon nanotubes and carbon nanofibers in the conductive material is a:b:c=0.8:0.6:0.4;

[0082] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.45g / cm 3 .

[0083] Embodiment 8:

[0084] The positive electrode active material is lithium manganese iron phosphate (LMFP), the conductive material is carbon black, carbon nanotubes and carbon nanofibers, and the binder is polyvinylidene fluoride (PVDF);

[0085] The mass ratio of positive electrode active material, conductive material and binder is W h :W d :W n =97.22:0.78:2; the mass ratio of carbon black, carbon nanotubes and carbon nanofibers in the conductive material is a:b:c=0.38:0.2:0.2;

[0086] The surface density of the positive electrode is SD = 500g / m 2 , the compaction density of the positive electrode sheet PD = 2.2g / cm 3 .

[0087] 2. Battery performance test

[0088] 1) DC internal resistance DCIR test

[0089] Test method: constant current and constant voltage charging, the current is 0.33C, the constant voltage is 4.2V, the cut-off current is 0.05C (C is the battery design capacity), after leaving for 0.5h, discharge at 0.1C for 0.5Q, leave for 1h, record the voltage at this time as V0, then discharge at 1C for 30s, record the voltage V1 and current I at the end of discharge, then DCR = (V0-V1) / I, the unit is mΩ.

[0090] The batteries of Examples 1 to 8 were subjected to a DC internal resistance (DCIR) test. The test results are shown in Table 1.

[0091] 2) Cycle performance test

[0092] Test method: leave for 30 minutes at 25°C; charge with constant current and constant voltage, the current is 0.33C, the constant voltage is 4.2V, and the cut-off current is 0.05C (C is the battery design capacity), and the capacity of the last cycle is Q rated capacity after three cycles; leave for 1 hour, charge with constant current and constant voltage, the current is 1Q, the constant voltage is 4.2V, and the cut-off current is 0.05Q; leave for 1 hour, discharge with constant current, the current is 1Q, and cycle 500 cycles. After 500 cycles, the stability of the material is evaluated by the cycle capacity retention rate. The battery cycle performance test results of Examples 1 to 8 are shown in Table 1.

[0093] Table 1

[0094]

[0095] In Table 1, the positive electrode active material represents lithium iron manganese phosphate, the binder represents polyvinylidene fluoride, the conductive agent a represents carbon black, the conductive agent b represents carbon nanotubes, and the conductive agent c represents carbon nanofibers.

[0096] From the data in Table 1, it can be seen that the W of Examples 1 to 6 n / (PD*W d ) calculated values ​​are all in the range of 0.27 to 1.12. The W of Example 7 n / (PD*W d ) calculated value is lower than the above range, W of Example 8 n

[0097] / (PD*W d ) calculated value is higher than the above range.

[0098] Example 1 is a more optimal ratio scheme of the present application. The battery capacity retention rate of Example 1 is as high as 96.1%, and the DC internal resistance is relatively low, which proves that the battery of Example 1 has a higher cycle capacity and better conductivity.

[0099] Compared with Example 1, the scheme of Example 2 increases the content of conductive agent and compaction density. The DC internal resistance of Example 2 is reduced, which proves that the increase of conductive agent content can improve the conductivity of the battery. The battery capacity retention rate of Example 2 is slightly reduced, which proves that the further increase of compaction density cannot further improve the battery capacity. This may be because the greater the compaction density, the greater the degree of compression between the electrode material particles, the smaller the porosity of the pole piece, and the reduced channels for ion transmission, resulting in large polarization losses during the battery cycle, affecting the battery cycle performance. However, the battery of Example 2 still has a higher cycle capacity and better conductivity as a whole.

[0100] Compared with Example 1, the conductive material of Example 3 only includes carbon black. The DC internal resistance of the battery of Example 3 is increased and the capacity retention rate is reduced. This is because the conductive material of Example 3 lacks a conductive network formed by a linear conductive agent, which results in reduced conductivity and reduced cycle performance.

[0101] Compared with Example 3, the scheme of Example 4 adds carbon nanotubes to the conductive material of Example 4, and the DC internal resistance of Example 4 is reduced and the capacity retention rate is increased. This is because the carbon nanotubes and carbon black form a conductive network, which improves the conductive properties of the conductive material and also improves the cycle performance.

[0102] Compared with Example 4, the content of carbon black in the conductive material of Example 5 is less than that of carbon nanotubes. The DC internal resistance of Example 5 is increased and the capacity retention rate is reduced. This is because the excessive content of carbon nanotubes makes it difficult to disperse the positive electrode active material particles and the carbon black particles, resulting in agglomeration, which in turn affects the conductive performance and cycle performance.

[0103] Compared with Example 1, the content of carbon black in the conductive material of Example 6 is less than that of carbon nanotubes, and the content of carbon black is less than that of carbon nanofibers. The DC internal resistance of Example 6 increases and the capacity retention rate decreases. This is because the carbon black content is too low and the conductivity is reduced. In addition, the carbon nanotubes and carbon nanofibers have too much content, which makes it difficult to disperse the positive electrode active material particles and carbon black particles, resulting in agglomeration, reducing the conduction efficiency, and causing the overall conductivity to decrease, which in turn affects the conductivity and cycle performance.

[0104] In the scheme of Example 7, W n / (PD*W d )≤0.27, its compacted density increases to 2.45g / cm 3 , the binder content is too low, which makes coating difficult and the positive electrode sheet cannot be made, so the solution fails.

[0105] In the scheme of Example 8, W n / (PD*W d )≥1.12, the binder content increases and the conductive agent content decreases, the DC internal resistance of Example 8 increases significantly, the capacity retention rate is as low as 92.1%, the conductive performance and cycle performance are poor, and the system is difficult to meet the long cycle requirements.

[0106] In the above embodiments, the description of each embodiment has its own emphasis. For parts that are not described in detail in a certain embodiment, reference can be made to the relevant descriptions of other embodiments.

[0107] The embodiments, implementation methods and related technical features of the present application can be combined and replaced with each other without conflict.

[0108] The above are only preferred embodiments of the present application and do not constitute any form of limitation to the present application. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present application without departing from the content of the technical solution of the present application are still within the scope of the technical solution of the present application.

Claims

1. A positive electrode sheet, characterized in that: It includes a positive electrode current collector and a positive electrode active material coating disposed on at least one surface of the positive electrode current collector; The positive electrode active material coating comprises a positive electrode active material, a conductive material and a binder; The compaction density PD of the positive electrode sheet and the content W of the conductive material d And the content of the binder W n The relationship satisfies: 0.27≤W n / (PD*Wd)≤1.

12.

2. The positive electrode sheet according to claim 1, characterized in that: The conductive material includes a main conductive agent and an auxiliary conductive agent, the main conductive agent is in a granular form, and the auxiliary conductive agent is in a linear structure.

3. The positive electrode sheet according to claim 2, characterized in that: The main conductive agent includes carbon black, and the auxiliary conductive agent includes at least one of carbon nanotubes and carbon nanofibers.

4. The positive electrode sheet according to claim 3, characterized in that: The conductive material includes carbon black and carbon nanotubes, wherein the mass percentage a of the carbon black is in the range of 0.3% to 1.8%, the mass percentage b of the carbon nanotubes is in the range of 0.2% to 0.8%, and a>b.

5. The positive electrode sheet according to claim 3, characterized in that: The conductive material includes carbon black and carbon nanofibers, wherein the mass percentage a of the carbon black is in the range of 0.3% to 1.8%, the mass percentage c of the carbon nanofibers is in the range of 0.2% to 0.8%, and a>c.

6. The positive electrode sheet according to claim 3, characterized in that: The conductive material includes carbon black, carbon nanotubes and carbon nanofibers, wherein the mass percentage a of the carbon black ranges from 0.3% to 1.8%, the mass percentage b of the carbon nanotubes ranges from 0.2% to 0.8%, the mass percentage c of the carbon nanofibers ranges from 0.2% to 0.8%, and a≥b≥c.

7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The thickness of the positive electrode sheet is d, 200 μm≤d≤250 μm; the surface density of the positive electrode sheet is SD, 480 g / m 2 ≤SD≤560g / m 2 The compaction density of the positive electrode is PD, 2.3g / cm 3 ≤PD≤2.5g / cm 3 .

8. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: The positive electrode active material includes lithium manganese iron phosphate.

9. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: In the positive electrode active material coating, the mass percentage of the positive electrode active material is in the range of 96% to 98%, the mass percentage of the conductive material is in the range of 0.8% to 1.8%, and the mass percentage of the binder is in the range of 1.2% to 2.2%.

10. A battery, characterized in that: It comprises the positive electrode sheet as claimed in any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-safety lithium manganese iron phosphate battery

    CN106129365A

  • Lithium ion battery pole piece

    CN110767875A

  • Cylindrical lithium ion battery with quick charging performance

    CN112002892A

  • High-voltage positive pole piece and lithium ion secondary battery comprising same

    CN112864360A

  • Positive pole piece with three-dimensional conductive network structure and preparation method of positive pole piece

    CN115117297A